Molecular analysis of weak D type in chinese blood donor from National Blood Center, Malaysia / Tressa Gadung Saptu - Saptu, Tressa Gadung (2016)
Most of studies on molecular basis of weak D have been conducted in Europe, Africa and several countries in Asia. Prevalent of weak D types varies among countries and also populations. Weak D type 15 was predominant in Chinese population in China. Meanwhile, there is limited data regarding weak D type in Chinese population in Malaysia. Therefore, present study was conducted to determine the weak D type in Chinese blood donors from National Blood Centre (NBC), Malaysia by molecular technique of polymerase chain reaction with specific sequence primer (PCR-SSP). A total of nine D-negative blood samples of Chinese blood donors collected from NBC were tested for Rh phenotypes, weak D phenotypes and weak D allele by using molecular technique of PCR-SSP. Rh phenotypes consist of of 4 (45%) of ce, 1 (11%) of Ce, 3 (33%) of Cce and 1 (11%) of cEe. Out of nine D-negative blood samples, two were positive for weak D phenotype. Weak D type 15 was identified from both samples that positive for weak D phenotypes. Cce and cEe were the Rh phenotypes that present with weak D type 15 samples. As a conclusion, weak D type 15 was identified from Chinese blood donors and it is the first type of weak D that observed in Malaysian Chinese.